Villanova University awarded Holmes Rolston the Mendel Medal on April 2, 2005 - Rolston, Holmes, 1932-2025, author; Unidentified photographer (Colorado State University. Libraries, 2005)
The Mendel Medal is given primarily to scientists to recognize their outstanding contributions to genetics and to science more generally with concern for the ethical and religious dimensions of their research.
Includes text of background information on the Medal, image of the Medal certificate, and photographs of Dr. Rolston receiving the Medal from Villanova University President Edmund J. Dobbin and giving speech at awards banquet.
Visit the Mendel Medal website http://www.villanova.edu/artsci/college/about/awards/mendelmedal/ for more information.
Keywords: Villanova University; Mendel Medal; Colorado State University; philosophy professor; Rolston, Holmes, 1932-2025; award